Application of Critical Success Factors in Supply Chain Management - Mohamed Syazwan Ab Talib; Abu Bakar Abdul Hamid (International Journal of Supply Chain Management, 2014)
This study is the first attempt that assembled published academic work on critical success factors (CSFs) in supply chain management (SCM) fields. The purpose of this study are to review the CSFs in SCM and to uncover the major CSFs that are apparent in SCM literatures. This study apply literature survey techniques from published CSFs studies in SCM. A collection of 42 CSFs studies in various SCM fields are obtained from major databases. The search uses keywords such as as supply chain management, critical success factors, logistics management and supply chain drivers and barriers. From the literature survey, four major CSFs are proposed. The factors are collaborative partnership, information technology, top management support and human resource. It is hoped that this review will serve as a platform for future research in SCM and CSFs studies. Plus, this study contribute to existing SCM knowledge and further appraise the concept of CSFs.